Answer:
![f'(x)=2x](https://img.qammunity.org/2020/formulas/mathematics/college/hqgm7dv0xd8ufx9rmfgzrrcxwzighrbgqi.png)
Explanation:
To Find :Find the derivative of the function by using the Product Rule. Simplify your answer. f(x) = (x - 3)(x + 3)
Solution :
![f(x) = (x - 3)(x + 3)](https://img.qammunity.org/2020/formulas/mathematics/college/zpvuks8fzg4x1huguxbnjc3mmv62ykmmx5.png)
We will use chain rule of product
Formula :
![uv=u * v' +v \tyimes u'](https://img.qammunity.org/2020/formulas/mathematics/college/sns5t7iyt0cmt6gua7gxw9zjukulwopgv9.png)
=
![(x-3) * 1+(x+3) * 1](https://img.qammunity.org/2020/formulas/mathematics/college/v0jknbou2n2bkaq5wlmd157ool4fzy24ej.png)
=
![(x-3)+(x+3)](https://img.qammunity.org/2020/formulas/mathematics/college/ntv3s2evg0dev6qznwmrauxw2o368o8b71.png)
=
![2x](https://img.qammunity.org/2020/formulas/mathematics/high-school/ehg1x3n3vnt1s4e4gae0epm9rgujr7wlmt.png)
So,
![f'(x)=2x](https://img.qammunity.org/2020/formulas/mathematics/college/hqgm7dv0xd8ufx9rmfgzrrcxwzighrbgqi.png)
Hence the derivative of the function by using the Product Rule is 2x